Clinical evaluation and management of badminton-related eye injuries: a retrospective case series - Tingting Guo; Wanru Shi; Xiuqian Yi; Tianrui Huang; Peijie Huang; Kang Xue (BMC Ophthalmology, 2023)
Abstract Background To describe the clinical features, visual outcomes, management, and complications of ocular injury in badminton and investigate risk factors associated with visual impairment. Methods Data on patients injured while playing badminton admitted to Department of Ophthalmology, Eye, Ear, Nose, and Throat Hospital, Fudan University between January 2018 to December 2020.The relationship between visual acuity (VA) and demographic and clinical variables was also analyzed. Patients were managed medically or surgically as per their needs, followed up for at least 18 months. The visual outcomes were predicted using ocular trauma score (OTS), predicted outcomes were compared with actual outcomes using statistical tests. Results This study involved 102 patients (78 men, 24 women) with a mean age of 43.8 ± 16.1 years (7–71 years). Of these, 93 patients had closed-globe injuries and 9 had open-globe injuries. Vision-threatening findings included lens subluxation(31.4%),retinal detachment(13.7%),hyphema(12.7%). Open-globe injury had significantly lower presenting VA and final VA (P= 0.0164, 0.0053).Final VA was found to be correlated with presenting VA, maculopathy, retinal detachment, and OTS (P=0.0000, 0.0494, 0.0001, 0.0000 respectively), it was worse in patients who were under 20 years of age and were female. OTS prediction was not significantly different when compared with actual visual outcomes postoperatively in OTS3, OTS4, and OTS5 (P > 0.05),while the prognosis of patients with OTS1 and OTS2 was better than OTS study (P=0.001, 0.007, respectively). Conclusion Badminton-related closed-globe injuries were more frequent; open-globe injuries were usually more serious. Younger and female patients have poorer visual recovery prognoses. OTS was found to be a reliable tool for predicting visual outcomes.